POPULASI DAN SERANGAN LALAT BUAH (Bactrocera spp.) PADA TANAMAN CABAI (Capsicum sp.) - Cecilia Wattimena; Muhammad R. Uluputty; Saartje H. Noya (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Fruit flies are important pests of agricultural crops in Indonesia. Fruit flies start attacking plants from the early stages of fruiting until the fruit is ready for harvest. This study aims to calculate the population of fruit flies (Bactrocera spp.) on cayenne pepper and curly pepper varieties. Obtain data on the intensity of damage caused by fruit fly (Bactrocera spp.) pests on cayenne pepper and curly pepper plants. This study was conducted in Talaga Kodok Hamlet for cayenne pepper plants and in Taeno Hamlet for curly pepper plants. This study was conducted from May to July 2025. This study used a survey method. The results showed that the population of fruit flies (Bactrocera spp.) was higher on cayenne pepper varieties Kara with an average of 295.3 individuals compared to curly pepper varieties Laju with 210.6 individuals. The intensity of damage was 9.42% on cayenne pepper varieties Kara and the intensity of damage on curly pepper varieties Laju at 18.38% both of which are classified as light criteria.